Hypoglycemic Effect of Some Ethnomedicinal Plants and Its Applications on Pancreas Improvement - Munem, Osama A.; Kasturi, Mahendran; Makky, Essam A.; Normaiza, Z.; Thanoon, Raid D.; M. M., Yusoff (Universiti Malaysia Pahang, 2017)

(untitled)
Diabetes is a disease that causes the blood glucose level to rise and if left untreated, could yield in many complications such as amputations of body parts, muscle disorders and fatigue. The alarming increase in the number of patients suffering from diabetes requests for more studies to be conducted to find alternatives in producing a cure to this disease. Many chemical methods are adapted towards the treatment of diabetes, so it is crucial that studies on medicinal plants are carried out to produce a solution that does not rely on chemicals alone, and can inhibit the diabetic activity as much as the existing medications. This study was conducted to collect and extract ethnomedicinal plants from Malaysia using different solvents, to select the most potent ethnomedicinal plant extract using anti-diabetic screening assays and to screen for combination effects of the plant extracts on anti-diabetic activity. The plant extracts are then subjected to α- amylase and assays whereby detection of potent plants that result in more than 50% inhibition is selected. Selected plants are combined to one another in dual, triple and quadruple plant extract combinations and anti-diabetic assays are performed once again to find the most effective combination that gives the highest inhibition value. Once the combined inhibition values are obtained, these values determined and classified into synergistic and antagonistic groups depending on its relationship with one another, whether it enhances inhibition value or not. For alpha-amylase inhibition, the chloroform extract of E. longifolia gave the highest inhibition of α-amylase enzyme at 82.42%.